Scalp metastasis of oesophageal adenocarcinoma: a rare case - Lata, Tahmina Jahan; Gahankari, Dilip; Arnold, Colin (International Surgery Journal, 2021)
Cutaneous metastases of oesophageal adenocarcinoma are uncommon. Several different sites of metastases including skin and lip has been reported. However, metastases to the scalp is an extremely rare event. We present a unique case of oesophageal adenocarcinoma metastasis to the scalp. Further, a discussion is offered on the mechanism of route of spread from the oesophagus to the scalp.